Acanthamoeba keratitis: a comprehensive review of pathogenesis, clinical manifestations, diagnostic challenges, and therapeutic strategies - Ramírez López, Diego Alejandro; Silva López, Donaldo Emiliano; Ramírez Ruiz, Ingrid Alejandra; Martínez Martínez, Adriana Lorena; Muñoz Campos, Belinda Margot Maruca; Salas Flores, Lesly Vanessa (International Journal of Research in Medical Sciences, 2025)
Acanthamoeba keratitis (AK) is a rare but severe ocular infection caused by the protozoan parasite Acanthamoeba spp., which poses significant diagnostic and therapeutic challenges. This condition is frequently associated with contact lens use, corneal trauma, or exposure to contaminated water. The pathogenesis of AK involves the adhesion of Acanthamoeba trophozoites to the corneal epithelium, followed by invasion and subsequent tissue destruction mediated by proteolytic enzymes and cytotoxic factors. Clinically, AK presents with symptoms such as severe ocular pain, photophobia, blurred vision, and a characteristic ring-shaped corneal infiltrate. However, its nonspecific early manifestations often lead to misdiagnosis or delayed treatment, exacerbating the risk of corneal perforation and permanent visual impairment. Diagnosis relies on a combination of clinical suspicion, microbiological techniques (e.g., corneal scrapings, culture, and confocal microscopy), and molecular methods such as PCR. Current therapeutic approaches include biguanides (e.g., polyhexamethylene biguanide), diamidines (e.g., propamidine isethionate), and adjunctive corticosteroids, although treatment resistance and recurrence remain significant concerns. This review aims to provide an in-depth analysis of the epidemiology, pathophysiology, clinical features, diagnostic modalities, and emerging therapeutic options for AK, emphasizing the need for early recognition and multidisciplinary management to improve patient outcomes.